2015
DOI: 10.1136/bmjopen-2014-007020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intentions to quit smoking in Aboriginal tobacco smokers of reproductive age in regional New South Wales (NSW), Australia: quantitative and qualitative findings of a cross-sectional survey

Abstract: ObjectivesTo assess the predictors of intentions to quit smoking in a community sample of Aboriginal smokers of reproductive age, in whom smoking prevalence is slow to decline.Design, setting and participantsA cross-sectional survey involved 121 Aboriginal smokers, aged 18–45 years from January to May 2014, interviewed at community events on the Mid-North Coast NSW. Qualitative and quantitative data were collected on smoking and quitting attitudes, behaviours and home smoking rules. Perceived efficacy for quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Psychological threats of disgust, regret and stigma about smoking have also been reported (Gould et al 2015c). Those who consider the threat to lack immediacy, believing 'smoking is not doing me any harm right now', are less motivated to quit (OR 0.25; 95% CI 0.08-0.8) (Gould et al 2015c). High-perceived efficacy (self-efficacy and response efficacy) for quitting was strongly associated with intention to quit (OR 4.8; 95% CI 1.78-12.93) (Gould et al 2015b), whereas low-perceived efficacy coupled with lowperceived threat (in 16%) was associated with denial, avoidance or reactance to messages (Gould et al 2015d).…”
Section: Intentions For Behaviour Change In Pregnancymentioning
confidence: 99%
See 4 more Smart Citations
“…Psychological threats of disgust, regret and stigma about smoking have also been reported (Gould et al 2015c). Those who consider the threat to lack immediacy, believing 'smoking is not doing me any harm right now', are less motivated to quit (OR 0.25; 95% CI 0.08-0.8) (Gould et al 2015c). High-perceived efficacy (self-efficacy and response efficacy) for quitting was strongly associated with intention to quit (OR 4.8; 95% CI 1.78-12.93) (Gould et al 2015b), whereas low-perceived efficacy coupled with lowperceived threat (in 16%) was associated with denial, avoidance or reactance to messages (Gould et al 2015d).…”
Section: Intentions For Behaviour Change In Pregnancymentioning
confidence: 99%
“…A community-based study revealed that a majority (77%) of Indigenous smokers of reproductive age perceived smoking to be highly threatening to physical health, implying that reflective motivation is occurring (Gould et al 2015c). Psychological threats of disgust, regret and stigma about smoking have also been reported (Gould et al 2015c).…”
Section: Intentions For Behaviour Change In Pregnancymentioning
confidence: 99%
See 3 more Smart Citations